1984
DOI: 10.1111/j.1365-2125.1984.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamics and plasma concentrations following sublingual GTN and intravenous, or inhaled, isosorbide dinitrate.

Abstract: CF44XN1 We measured plasma nitrate levels and haemodynamics following sublingual glyceryl trinitrate (GTN) (0.5 mg), or isosorbide dinitrate (ISDN) administered intravenously (0.5 mg) or by inhalation (1.25 mg) in 23 patients undergoing cardiac catheterisation for investigation of chest pain. 2 Peak levels were detected at 90 s and 5 min following intravenous and inhaled ISDN respectively and at 3 min following sublingual GTN. 3 Intravenous and inhaled ISDN produced similar plasma levels at 30 s and both were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our study is in agreement with previous reports that showed that GTN exposure in cultured endothelial cells leads to the accumulation of citrulline, indicative of nitric oxide synthase activation [8]. It also concurs with other studies that demonstrated that the rapid action of GTN is coincident with its peak concentrations in the plasma rather than with its lower nitrate metabolites [23,24]. Further support to the idea that eNOS intermediates nitroglycerin-induced vasodilation is found in early reports showing the endothelium dependence of GTN effects in animals and human patients [9,10,12].…”
supporting
confidence: 93%
“…Our study is in agreement with previous reports that showed that GTN exposure in cultured endothelial cells leads to the accumulation of citrulline, indicative of nitric oxide synthase activation [8]. It also concurs with other studies that demonstrated that the rapid action of GTN is coincident with its peak concentrations in the plasma rather than with its lower nitrate metabolites [23,24]. Further support to the idea that eNOS intermediates nitroglycerin-induced vasodilation is found in early reports showing the endothelium dependence of GTN effects in animals and human patients [9,10,12].…”
supporting
confidence: 93%
“…However, the majority of the hemodynamic effects would be expected to have occurred within the first 2 minutes of administration. 33 …”
Section: Discussionmentioning
confidence: 99%
“…(iii) Physical exercise involved running on the spot for 100 steps and an ECG was recorded when subjects were lying supine immediately after the exercise. After a further 45‐min supine rest, subjects were given a 0.5‐mg GTN tablet sublingually and remained supine for 3 min, when an ECG was recorded, corresponding to T max for sublingual GTN [13]. They were then asked to stand for 3 min when an ECG was recorded, after which they remained supine for the remainder of the study.…”
Section: Methodsmentioning
confidence: 99%